A study of plasma power effects on surface activation of polystyrene. (April 2021) - Chen, Ting-Hao; Chung, Fang-Yi; Jiang, Wei-Fan; Huang, Chun
Abstract: In this study, polystyrene (PS) surface activation was performed with cyclonic atmospheric-pressure plasma to improve surface hydrophilicity, and the effects of plasma power on cyclonic plasma surface activation were investigated. Altered PS surface characteristics were observed through a wettability analysis. The PS surface hydrophilicity was highly enhanced during the cyclonic plasma treatment. The substantial growth of the PS surface hydrophilicity was attributed to the crosslinking by activated species of inert gases due to the presence of cyclonic plasma. Optical emission spectroscopy was used to determine various chemical plasma species and the association of the plasma surface treatment with the changes in the electron density and electron excitation temperature in cyclonic plasma with increasing plasma power. X-ray photoelectron spectroscopy (XPS) and atomic force microscopy were used to determine the chemical and morphological variations on the cyclonic plasma-treated PS surface. The XPS analysis exhibited noticeably higher surface concentrations of oxygen functional groups on the cyclonic plasma-activated PS surface compared to the untreated PS. The results show that cyclonic plasma is an operative plasma device that can be used to improve PS surface hydrophilicity. Graphical abstract: To improve surface hydrophilicity, the polystyrene surface activation was carried out with cyclonic plasma at atmospheric pressure and the power effect on plasma surface activation was investigated. Optical emission spectroscopy was used to determine chemically plasma species and the association of polystyrene surface activation with the change of electron density and electronic excitation temperature in cyclonic plasma by increasing plasma power. Image 1 Highlights: Cyclonic plasma enhances the surface hydrophilicity of polystyrene. The polar functional groups from plasma surface activation cause increased surface energy of polystyrene. Effects of plasma treatment factors on polystyrene were studied. Cyclonic plasma can be used as the effective surface activation for polystyrene.